2013
DOI: 10.1158/0008-5472.can-12-2489
|View full text |Cite
|
Sign up to set email alerts
|

BRMS1 Suppresses Lung Cancer Metastases through an E3 Ligase Function on Histone Acetyltransferase p300

Abstract: The mechanisms through which the metastasis suppressor gene BRMS1 functions are poorly understood. Herein, we report the identification of a previously undescribed E3 ligase function of BRMS1 on the histone acetyltransferase p300. BRMS1 induces polyubiquitination of p300 resulting in its proteasome-mediated degradation. We identify BRMS1 as the first eukaryote structural mimic of the bacterial IpaH E3 ligase family, and establish that the evolutionarily conserved CXD motif located in in BRMS1 is responsible fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 43 publications
1
34
0
Order By: Relevance
“…In support of our observation regarding activation of selective EMT-TFs, Pantuck and colleagues demonstrated that loss of VHL activity stimulated renal cell carcinoma cells to activate NF-B and promote EMT through selective upregulation of Twist1 and Slug but not Snail, Zeb1, or Zeb2 (53). Interestingly, both BRMS1 and VHL can function as E3 ubiquitin ligases to suppress tumor progression (29,54). Therefore, one plausible explanation of these observations is that the targets of E3 ligases BRMS1 and VHL, such as p300 and HIF1␣, respectively, contribute to NF-B-mediated selective upregulation of Twist1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of our observation regarding activation of selective EMT-TFs, Pantuck and colleagues demonstrated that loss of VHL activity stimulated renal cell carcinoma cells to activate NF-B and promote EMT through selective upregulation of Twist1 and Slug but not Snail, Zeb1, or Zeb2 (53). Interestingly, both BRMS1 and VHL can function as E3 ubiquitin ligases to suppress tumor progression (29,54). Therefore, one plausible explanation of these observations is that the targets of E3 ligases BRMS1 and VHL, such as p300 and HIF1␣, respectively, contribute to NF-B-mediated selective upregulation of Twist1.…”
Section: Discussionmentioning
confidence: 99%
“…BRMS1 has been shown to function as a corepressor to inhibit NF-B transactivation through deacetylation of the RelA/ p65 subunit at K310 (25). Additional mechanisms by which BRMS1 functions include the regulation of phosphoinositide signaling (26), expression of microRNA (miRNA) (27), angiogenesis (28), and p300 histone acetyltransferase levels (29). Whereas metastasis suppressor family members NM23, CD44, MKK4, and Kiss1 have been shown to regulate EMT, the role of BRMS1 in EMT has not been previously explored.…”
mentioning
confidence: 99%
“…First identified in 2000 (16), the gene suppresses the metastasis of breast carcinoma cells to lungs and regional lymph nodes. Subsequent studies indicated that BRMS1 mediated inhibition of metastasis in multiple types of human cancer, including GC (17)(18)(19)(20). A number of studies have confirmed that a number of protein-coding genes are regulated by miR-125a-5p in different types of human cancer (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…SIN3 proteins can link HDAC and co-repressors to chromatin-bound transcription factors to inhibit target gene expression 9,10 . Downregulation of breast cancer metastasis suppressor 1 (BRMS1), a major co-repressor interacting with Sin3A, is associated with metastasis of multiple types of malignancies, including breast, nasopharyngeal, melanoma, non-small-cell lung cancinomas and melanomas [11][12][13][14][15] . Moreover, transfection of BRMS1 into highly metastatic human breast cancer cell lines significantly inhibited lung metastasis in xenografted mice without influencing orthotopic tumour incidence and growth rate, suggesting that BRMS1 is a metastasis suppressor 16 .…”
mentioning
confidence: 99%